Characterization of the Beauveria bassiana ga fungal strain isolated from the muscardine infected silkworms (Bombyx mori L.) - Nguyen Giang Van; Nguyen Quynh Anh; Hien Pham Hong; Pylnev V.V. (E3S Web of Conferences, 2024)
In this study, the focus was on isolating and characterizing the fungal strain Beauveria bassiana from muscardine-infected silkworms (Bombyx mori L.). The fungal strain isolated from the muscardine-infected silkworm, designated as GA, closely resembled Beauveria bassiana isolate SBI-Bb04 based on morphological analysis and comparison of the 18S rRNA nucleotide sequence with sequences in the NCBI database. Beauveria bassiana GA demonstrates the ability to grow on Sabouraud Dextrose Agar (SDA) medium. Optimal conditions for its growth were determined to be a pH range of 6-7 and a temperature range of 20-25°C. The composition of SDA, containing glucose and peptone sources, was found to be ideal for both growth and sporulation of this fungal strain. Furthermore, Beauveria bassiana GA exhibits the capacity to synthesize various extracellular enzymes, including chitinase, protease, cellulase, and amylase. These enzymatic activities contribute to its pathogenicity and suggest its potential as a biocontrol agent against insect pests.